Clinical Cancer Bulletin - Fan, Jia.; Wang, Xiangdong; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer.)
Clinical Cancer Bulletin (CCB) was launched in 2022 by its founding Editor-in-Chief, Prof. Jia Fan, CAS member, a well-known hepatobiliary surgery expert and cancer researcher from Zhongshan Hospital, Fudan University. CCB is an international, peer-reviewed open access journal covering international issues relevant to clinical cancer specialists worldwide. A strict and rigorous anonymous peer-review procedure ensures the quality and consistency of articles submitted by clinical cancer researchers. CCB strives to report original, innovative, high quality and timely contents in clinical oncology and deliver the most credible, authoritative cancer research information to clinical cancer specialists. CCB is concerned about, but not limited to, the following scopes: disseminating high-quality publications on clinical cancer research, including medical oncology, surgical oncology, and radiation oncology; delivering innovative research findings on cancer or translated works related to clinical oncology and precision medicine; focusing on clinical trials evaluating new treatments, accompanied by researches on pharmacology, and molecular alterations or biomarkers that predict response or resistance to the treatments; representing and advancing the profession of clinical cancer research throughout the world; promoting high-quality multidisciplinary patient care worldwide; improving global oncology education and training; promoting diversity in all of its endeavors.
Keywords: Oncology; Cancer; Medicine; Oncology; Cancers; Clinical Medicine